Investigasi Penerapan Keringanan Keterlambatan terhadap Pelunasan Pembiayaan Murabahah di BPRS Bhakti Sumekar Pragaan - Moh. Helmi Hidayat; Romsiyeh (Universitas Muhammadiyah Surabaya, 2024)
Abstract BPRS Bhakti Sumekar, Pragaan branch, one of the shari'ah banks that adopt Murabahah financing with the principle of a sale and purchase contract as one of the products provided to customers. This research was lifted from the problems described in 2 research focuses, namely: 1. What are the factors that cause delays in repayment of Murabahah at BPRS Bhakti Sumekar Pragaan Branch? 2. How is the implementation of late payment relief for BPRS Bhakti Sumekar Pragaan Branch customers?. To find out more deeply what are the factors that cause delays in repayment of Murabahah and how to apply late payment relief for customers at BPRS Bhakti Sumekar Pragaan Branch, researchers used a field qualitative approach. The method used is the method of observation, interviews, and documentation. The factors that cause delays in repayment of Murabahah at BPRS Bhakti Sumekar Pragaan Branch, namely, there are two factors, First, Internal factors, namely from the bank itself, Second, External factors from the customer himself, where, the customer has experienced a decrease in his business, there is a disaster, etc. Meanwhile, the application of late repayment relief for customers of the Pragaan Branch of BPRS Bhakti Sumekar, namely, with 3R, (Restructuring, Rescheduling, Reconditioning) aims to correct and save delays in financing repayment. Keywords: Delay Factor, Application Of Relief, Murabahah Financing